AeU Focuses on Asian Business - Yee, Jie Min (The Sun, 2014)
Many in the West are talking about Asia - Why we are more successful and doing well. Right now we are thinking about being more focused and doing it successfully through our affiliation with Asian countries, so people can study the Asian market, business, and management - Prof Dr Juhary Ali